2016
DOI: 10.1111/fcp.12195
|View full text |Cite
|
Sign up to set email alerts
|

Cilostazol exerts antiplatelet and anti‐inflammatory effects through AMPK activation and NFkB inhibition on hypercholesterolemic rats

Abstract: This work presents a model of rats fed a high-cholesterol diet, receiving a long-term oral administration of cilostazol, a PDE3-inhibitor. The aim of this study was to evaluate the molecular mechanisms by which cilostazol interferes with platelets signaling pathways to avoid atherosclerosis early development. Male Wistar rats were divided into 3 groups: Control group received standard rat chow (C), hypercholesterolemic group (HCD), and HCD+CIL (cilostazol group) received hypercholesterolemic diet for 45 days. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 37 publications
3
26
0
Order By: Relevance
“…However, clinical data suggest that PDE3 inhibition therapy given via infusion in heart failure, bypass operations, and enterovirus 71 infection did show antiinflammatory effects (37)(38)(39). During the last decade, a growing number of studies suggest that PDE3 inhibition might be involved in immunosuppression (40)(41)(42)(43)(44)(45)(46)(47)(48), although there is no definitive proof. There have been concerns that PDE3 inhibitors were associated with increased cardiovascular mortality in previous clinical trials (49,50).…”
Section: Introductionmentioning
confidence: 99%
“…However, clinical data suggest that PDE3 inhibition therapy given via infusion in heart failure, bypass operations, and enterovirus 71 infection did show antiinflammatory effects (37)(38)(39). During the last decade, a growing number of studies suggest that PDE3 inhibition might be involved in immunosuppression (40)(41)(42)(43)(44)(45)(46)(47)(48), although there is no definitive proof. There have been concerns that PDE3 inhibitors were associated with increased cardiovascular mortality in previous clinical trials (49,50).…”
Section: Introductionmentioning
confidence: 99%
“…However whether cilostazol could be used as a potential drug to target DCs warrants further study. Some reports have shown that the effect of cilostazol is associated with the activation of the AMPK pathway, and this effect has been validated in various models [20,21,24,25]. Furthermore, AMPK has been suggested to play an important role in TLRs-induced IL-23 production [26].…”
Section: Discussionmentioning
confidence: 92%
“…3, IL23A promoter activity was * P < 0.05 vs. zymosan alone, ** P < 0.01 vs. zymosan alone, # P < 0.05 vs. cilostazol plus zymosan treatment. [20,21]. Thus, we aimed to clarify whether the inhibitory effect of cilostazol on IL-23 production by mo-DCs was mediated by AMPK by treating cells with an AMPK agonist (A-769662) and an AMPK antagonist (Compound C).…”
Section: Cilostazol Inhibited Myd88-induced Il23a Transcriptional Actmentioning
confidence: 99%
“…However, platelet activation and aggregation induced by membrane receptor P2Y 12 , adenosine diphosphate or platelet glycoprotein IIb/IIIA cause thrombosis, atherosclerosis, systemic inflammation, and cancer DOI: 10.1159/000499335 [2,3]; thus, the blockade of platelet activation is important for therapeutic field. Cilostazol, an inhibitor of platelet aggregation, has been used to treat patients with peripheral vascular disease and coronary interventions, due to its anti-inflammatory and anti-atherosclerotic properties [4,5]. Clopidogrel, a prodrug, is converted to its active form by the cytochrome P450 3A4 (CYP3A4) pathway in the liver, and the active metabolite exerts antiplatelet effect by inhibiting the P2Y 12 receptor [6].…”
Section: Introductionmentioning
confidence: 99%